2004
DOI: 10.3171/jns.2004.101.1.0128
|View full text |Cite
|
Sign up to set email alerts
|

Life span extension and reduced neuronal death after weekly intraventricular cyclosporin injections in the G93A transgenic mouse model of amyotrophic lateral sclerosis

Abstract: Treatment with CsA significantly delayed the onset of hindlimb weakness and also extended the time from its onset to paralysis. The overall life span of CsA-treated G93A mice was significantly extended, by 12% compared with vehicle-treated transgenic littermates. The CsA also prolonged physical performance on the exercise wheel and delayed weight loss. Histologically, there was significant preservation of both cervical and lumbar spine motor neurons and also tyrosine hydroxylase-positive dopaminergic substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…Nevertheless, CsA and its analogs have been among the most convincing and broadly effective group of drugs displaying neuroprotective properties in several diverse models of acute and chronic neurological disease. Pharmacological studies using CypD inhibitors in animal models have in particular implicated mPT in the pathogenesis of focal and global ischemia (Domanska-Janik et al, 2004;Matsumoto et al, 1999;Uchino et al, 1998;Yoshimoto and Siesjö , 1999), hypoglycemic brain damage (Friberg et al, 1998), TBI (Buki et al, 1999;Mbye et al, 2009;Sullivan et al, 2000), and ALS (Karlsson et al, 2004;Keep et al, 2001;Kirkinezos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, CsA and its analogs have been among the most convincing and broadly effective group of drugs displaying neuroprotective properties in several diverse models of acute and chronic neurological disease. Pharmacological studies using CypD inhibitors in animal models have in particular implicated mPT in the pathogenesis of focal and global ischemia (Domanska-Janik et al, 2004;Matsumoto et al, 1999;Uchino et al, 1998;Yoshimoto and Siesjö , 1999), hypoglycemic brain damage (Friberg et al, 1998), TBI (Buki et al, 1999;Mbye et al, 2009;Sullivan et al, 2000), and ALS (Karlsson et al, 2004;Keep et al, 2001;Kirkinezos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Using a transgenic mouse model of ALS (SOD1-G93A) in which weakness appears at 3 months of age, and death by 5 months, Keep et al (2001) and Karlsson et al (2004) showed that intraventricular administration of CsA prolonged the survival of these mice as compared to vehicle-treated controls. Histologically, there was significant preservation of cervical and lumbar spine motor neurons…”
Section: Degenerative Diseasesmentioning
confidence: 99%
“…For example, despite the deep differences between apoptosis and necrosis, the mitochondrial permeability transition pore (mPTP) was found to be involved in both types of cell death, but since the mPTP can be blocked by the CyPD/CsA complex, then cells are protected from injury and death [149]. Pharmacological targeting of the cyclophilins could be useful for treatments of Alzheimer [148], Huntington's disease [150], amyotrophic lateral sclerosis [151], and congenital muscular dystrophy [152], whereas CsA in aerosol form could be useful in the treatment of asthma [153] and airway inflammations [154]. Despite more than twenty-five years of research on the cyclophilins and their ligands still relatively few cyclophilins have been thoroughly investigated and many singular findings have never been independently confirmed or exploited [3,4].…”
Section: Cyclophilins Intra-cellular Signaling and Development Of Camentioning
confidence: 99%